1989
DOI: 10.1002/jso.2930420408
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of cervical lymph node biopsy: A pathological study of 596 cases

Abstract: During a 10-year period (1976-1985), a total of 596 cervical lymph node biopsies for diagnostic purposes were performed at our institution. Thirty-five percent of these nodes were involved with malignant lymphoma, and 20.5% showed metastatic deposits. Nondiagnostic reactive hyperplastic changes were noted in 23% of the cases. Several other inflammatory and neoplastic conditions were encountered. Comparison of our data with several series from different countries with review of relevant literature are presented. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

1989
1989
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Similarly, granulomatous lymphadenopathy due to tuberculosis was the most frequent diagnosis (37.9%) observed in one study from Saudi Arabia [4]. In another study, granulomatous conditions accounted for 28% of the cases [10]. However, that study did not specifically identify the granulomas as positive for tuberculosis.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Similarly, granulomatous lymphadenopathy due to tuberculosis was the most frequent diagnosis (37.9%) observed in one study from Saudi Arabia [4]. In another study, granulomatous conditions accounted for 28% of the cases [10]. However, that study did not specifically identify the granulomas as positive for tuberculosis.…”
Section: Discussionmentioning
confidence: 90%
“…These studies included all age groups; however, other studies have included adult patients only [4]. In a study from Jordan, 35% of the lymph nodes excised revealed malignant lymphoma, and 20.5% revealed metastatic deposits [10]. A comparison of the different studies is shown in Table 2.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Several studies on peripheral lymphadenopathy in various countries have shown that cervical lymph nodes are the most frequently enlarged and biopsied nodes of all peripheral lymph nodes. 1,2 Cervical lymphadenopathy is usually defined as cervical lymph nodal tissue measuring more than 1 cm in diameter. 3 This can be presented as isolated or as a part of generalized lymphadenopathy.…”
mentioning
confidence: 99%
“…Sarcoidosis is considered rare in Saudi Arabia and other Middle Eastern countries, 23,24 though recent findings reported from Jordan show that it is not as rare as it was thought to be. 25 Therefore, most of the cases of granulomatous lymphadenitis encountered in our study must be tuberculous in origin, though other causes should be considered.…”
Section: Discussionmentioning
confidence: 78%